2000
DOI: 10.1007/s005400050067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane anesthesia combined with epidural block on renal function in the elderly: comparison with isoflurane

Abstract: In both groups, glomerular and tubular function were transiently affected, but no abnormalities were found in routine laboratory tests, suggesting that neither isoflurane nor sevoflurane in combination with dopamine and epidural anesthesia seriously affects renal function in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Similar results in elderly patients subjected to isoflurane and sevoflurane anaesthesia were reported by Hase et al (26). Therefore, it seems that DNA damage inflicted following exposure to both anaesthetics was of transient nature, and it is obviously present in the first hours post exposure but is mostly effectively repaired later on, without producing severe functional impairments.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results in elderly patients subjected to isoflurane and sevoflurane anaesthesia were reported by Hase et al (26). Therefore, it seems that DNA damage inflicted following exposure to both anaesthetics was of transient nature, and it is obviously present in the first hours post exposure but is mostly effectively repaired later on, without producing severe functional impairments.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies suggest that in humans 2-5 % of the absorbed dose of sevoflurane is metabolised, compared to only 0.2 to 2 % of isoflurane (3,25). Second, it is important to mention that sevoflurane biotransformation results in the formation of inorganic fluoride and the so-called compound A, which are both considered toxic and, especially, nephrotoxic (25,26). Goldberg et al (27) found that sevoflurane biotransformation resulted in the generation of greater amounts of fluoride ions than isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Conversions to mgÁdL -1 were done for creatinine 24,34,55,61,64,68 and BUN 24,55,61,64,67,70 from non-SI units of measurements while conversions to mean (SD) for central tendency and dispersions were needed in four more studies. 57,64,68,70 Creatinine values were extrapolated from graphical data in seven studies, 49,51,54,56,69,71,72 BUN in eight studies, 43,49,51,54,56,69,71,72 CCR in eight studies, 39,40,43,49,53,56,60,68 and peak serum fluoride in 18 studies. 35,36,39,40,42,43,[48][49][50]55,[58]…”
Section: Resultsmentioning
confidence: 99%
“…57,64,68,70 Creatinine values were extrapolated from graphical data in seven studies, 49,51,54,56,69,71,72 BUN in eight studies, 43,49,51,54,56,69,71,72 CCR in eight studies, 39,40,43,49,53,56,60,68 and peak serum fluoride in 18 studies. 35,36,39,40,42,43,[48][49][50]55,[58][59][60][61]65,68,69,73 Risk of bias assessment…”
Section: Resultsmentioning
confidence: 99%
“…Carboplatin is excreted via glomerular filtration and active renal tubular transport, 23 and healthy Beagles have been documented to have decreased glomerular filtration rate (GFR) with medetomidine anesthesia 24 . Additionally, mild, transient glomerular and tubular functional impairment has been noted after anesthesia with sevoflurane or isoflurane in elderly human patients 25 . Furthermore, carboplatin dosage reductions are recommended in people with reduced creatinine clearance 26 .…”
Section: Discussionmentioning
confidence: 99%